Normal Ultrasonographic Renal length in relation to Glomerular Filtration rate among students in Universiti Malaysia Sabah - Ohnmar Myint; Thwe, Thwe See; Kyi, Kyi San; Than Myint; Thiri Tun (Universiti Malaysia Sabah, 2007)
Variation in kidney size occurs in many renal diseases and considered as important indicator in evaluation of these problems. Our study aims to set a normal range of kidney lengths among healthy young adult University students in UMS and will act as an input for further research to establish a normal range in people in sabah states. Total 321 UMS students from different programs were participate in this study. The ages range from 19 to 25 year. Both male and female are included the number of female participants (66%) are greater than male (34%) students. Chinese constitute 32.7%,Malay 24%,Kadazan 10.9%,Indian 3.7% and so on. The largest religious group is Islam ( 38.5% ). The mean BMI of 320 students is 21.35 ± S.D 3.58. Ultrasonographic renal measurements reveal the mean length in BMI of right and left kidneys of the students are almost the same i.e., 9.81±O.75 BMI and 9.85±O.58 BMI respectively.It will also exclude kidney pathology detected by ultrasonography despite the normal findings of physical examination and laboratory function tests.Thus it will improve awareness of possibilities kidney diseases which can be present in apparently normal healthy adults.